Therapeutic Self-Narration: Social Media for the Construction of Autistic Identities and Communities (Altre Modernità, 2024)
This paper analyzes how social media can serve as a space for practicing therapeutic self-narration about disability, specifically autism. Today, social media offer many individuals a fertile ground for promoting identity and community emancipation. This is particularly true when it comes to autism, which, like many disabilities, is often marginalized by society. Specifically, by examining the perspectives of three autistic women –@Autistic_Red_fryk_hey, @Lunnylunnylunny, and @La_panzer– it will be shown how the features of the Instagram platform facilitate the narration of their condition. The three creators aim to provide advice and teachings to promote awareness and dissemination among neurotypical individuals and help others on the spectrum find a space in their profiles to identify themselves. Utilizing different skills and qualities, these women use Instagram as a training ground for therapeutic work aimed at themselves and other users, creating content of high ethical and aesthetic value. Thus, social media emerge as effective tools for developing beneficial communication that reaches a broad and diverse audience, allowing the voices of those directly involved, often excluded from official debates, to be heard.
Keywords: Autism; Social media; Instagram; Self-representation; Self-narration; Identity